Pattern Leadership Khulafaur Rasyidin: Analysis History and Valuesfor Modern Life - Muhammad Amiruddin; Djibril Ganggo r; Nur Afiidah; Moch Dani Maulana; Farel Adityapurwoko (Journal of Humanities Research Sustainability, 2025)
Background. After the death of Prophet Muhammad SAW, Islamic civilization underwent a significant transitional phase under the leadership of the Khulafaur Rasyidin: Abu Bakar Ash-Shiddiq, Umar bin Khattab, Uthman ibn Affan, and Ali ibn Abi Talib. These leaders applied the noble values and teachings of Islam to ensure social stability and to expand Islamic civilization across various regions of the world. Their era marked a critical period of consolidation and ethical governance in the Islamic world. Purpose. The main purpose of this study is to explore the implementation of key leadership values during the Khulafaur Rasyidin period. These include justice, consultation (shura), responsibility, humility, and leading by example, all of which were essential in shaping a stable and morally grounded Islamic society. Method. This research uses a literature review method by collecting data from classical Islamic historical texts and relevant scholarly literature. The analysis focuses on identifying leadership traits and values demonstrated during the early caliphate period. Results. The study reveals that the leadership principles upheld by the Khulafaur Rasyidin significantly contributed to social cohesion, justice, and the overall welfare of the Muslim community during their reign. These values have shown continued relevance and adaptability to modern contexts of ethical leadership. Conclusion. The legacy of Khulafaur Rasyidin's leadership offers valuable insights for contemporary leaders. By adopting their values, today’s leaders can strengthen their connection with the people, prioritize justice, and uphold social responsibility in governance.